Law Enforcement Against Perpetrators of Illegal Charges Perpetrated by Civil Servants (Case Study of the Makassar District Attorney) - Ismail A. Rauf; Abd. Azis; Hijrah Adhyanti Mirzana (IHSA Institute, 2022)
Law enforcement against perpetrators of illegal levies committed by civil servants that occurred in Makassar has not been firmly enforced with penalties in accordance with the law. This research is an empirical normative research, combining a normative legal approach to legislation with empirical elements in the form of interviews. The results of the study indicate that law enforcement against criminal acts of Corruption with the Modus Operandi of carrying out illegal levies (Pungli) by Civil Servants and State Organizers is currently still limited to the application and enforcement of the provisions of Article 12 letter e of the Republic of Indonesia Law Number 31 of 1999 regarding the Eradication of Criminal Acts of Corruption as amended and added to the Law of the Republic of Indonesia Number 20 of 2001, this is due to an understanding by Law Enforcement Officials who are of the view that illegal levies have nothing to do with State Financial Loss, and (2) In the context of In the author's research, the Makassar District Attorney has many factors that affect the enforcement of illegal levies, as follows, namely the Law Factor, Law Enforcement Factor, Facilities or Facilities Factor, Factors society, cultural factors